2022
DOI: 10.1021/acs.jpcc.2c05572
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Quantum Interference in Molecular Devices Based on Molecular Conductance Orbitals

Abstract: Electron propagation through a molecular device is determined by its quantum electronic structure. We employ molecular conductance orbitals (MCOs) to predict and interpret quantum interference (QI), which contain more information about the electrodes compared with molecular orbitals (MOs) of an isolated molecule. The phases, amplitudes, and alignment of MCOs determine whether they interfere constructively or destructively, which can be seen directly from projection transmissions and QI maps. We apply this intu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The investigation of molecular projected self-consistent Hamiltonian (MPSH) further supports the combination feature. According to the theoretical studies, , the conductance could be mainly considered the sum of electron transport on HOMO and LUMO, which are independent of each other. As shown in Figure S7, it is noticed that, at the energy level of the LUMO for molecule 3 , there is an explicit projection on the channel of the meta-site of the phenyl group, indicating the major contribution of the electron transport on the channel of the meta-site.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The investigation of molecular projected self-consistent Hamiltonian (MPSH) further supports the combination feature. According to the theoretical studies, , the conductance could be mainly considered the sum of electron transport on HOMO and LUMO, which are independent of each other. As shown in Figure S7, it is noticed that, at the energy level of the LUMO for molecule 3 , there is an explicit projection on the channel of the meta-site of the phenyl group, indicating the major contribution of the electron transport on the channel of the meta-site.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, according to previous theoretical studies , and the reported conductance enhancement, which are all about 0.3 order with the dominated energy levels changing less than 1 eV, ,,, the energy shift of about 0.7 eV from molecule 1 to molecule 3 alone cannot afford the conductance enhancement of about 1.5 orders of magnitude. Thus, the coupling between the molecule and the electrodes, which is another crucial parameter in Landauer’s theory to determine the conductance, , was analyzed to explore the origin of conductance enhancement.…”
Section: Resultsmentioning
confidence: 58%
“…Thus, it is clear that the low-bias conductance of molecules 1−3 is mainly determined by LUMO, and the decrease of the energy level of LUMO from molecule 1 to molecule 3 improves the alignment of the frontier molecular orbitals relative to the Fermi energy of the electrodes to enhance the conductance. 11,35 However, according to previous theoretical studies 36,37 and the reported conductance enhancement, which are all about 0.3 order with the dominated energy levels changing less than 1 eV, 11,12,35,38−40 the energy shift of about 0.7 eV from molecule 1 to molecule 3 alone cannot afford the conductance enhancement of about 1.5 orders of magnitude. Thus, the coupling between the molecule and the electrodes, which is another crucial parameter in Landauer's theory to determine the conductance, 36,41 was analyzed to explore the origin of conductance enhancement.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…Inspired by molecular orbitals analysis theories, we have developed a new method for predicting and understanding the electronic transport properties based on molecular conductance orbitals (MCOs), which contain more information related to electrodes than MOs. To differentiate from MOs, we name occupied MCOs from high to low O1, O2, etc., and unoccupied MCOs from low to high U1, U2, etc.…”
Section: Methodsmentioning
confidence: 99%